Human ecology : following nature's lead - Steiner, Frederick R. (Island Press : Made available through hoopla, 2013)
In Human Ecology, noted landscape planner Frederick Steiner presents a historical and analytical examination of how humans interact with each other as well as with other organisms and their surroundings.